Parasocial mourning and political ritual: the case of Charlie Kirk - Madsen, Dag Øivind (Frontiers in Communication, 2026)
This paper examines parasocial mourning, mediated intimacy, and the emotional repertoires that shaped the public response to Charlie Kirk’s 2025 assassination. Drawing on news coverage, social media posts, and public statements, the analysis shows how grief, anger, fear, and hope were expressed and circulated in ways that made the loss feel both personal and political. The paper clarifies how mediated intimacy, symbolic elevation, and forms of collective expression took shape in the aftermath, and distinguishes these dynamics from esthetic elements rooted in evangelical culture. It also highlights how practices of remembrance, shared symbolism, and boundary enforcement sometimes resembled secular religious forms without implying theological equivalence. The paper concludes by outlining the implications of parasocial politics for democratic practice and platform-mediated political engagement.